Concussive injuries in Rugby 7s: a American experience and current review - Lopez, V. Jr.; Ma, R.; Weinstein, M. G.; Cantu, R. C.; Myers, L. S. D.; Nadkar, N. S.; Victoria, C.; Allen, A. A. (Medicine & Science in Sports & Exercise, 2016)
Purpose: There is a comparative lack of concussion incidence data on the new Olympic sport Rugby 7s. This study aimed to determine the incidence (number of concussions per 1000 playing hours [ph]), mean and median severity (days absence), and cause of concussive injuries.